The Influence of Intellectual Capital and Innovation on the Performance of SOEs in the Banking Sector in Indonesia - Reynaldi, Daniel; Wijaya, Chandra (Technium Social Sciences Journal, 2022)
Purpose- This study aims to determine the effect of intellectual capital, which includes Human Capital (HC), Structured Capital (SC), Capital Employed (CE), and innovation on the performance of SOEs in the Banking Sector in Indonesia Methodology- This study uses various research and secondary data from journals and books. Findings- The findings indicate that Intellectual capital, including Human Capital, Structural Capital and Capital Employed, relates positively to organisational performance in the banking sectors. The results also support the argument that innovation played an important role in organisational performance in the banking sectors. Research Implications- This study limits its generalisations since it is limited to the effect of intellectual capital and innovation on the performance of the company (issuer) in SOEs in the Banking Sector. Practical Implications- The present study provides insight and knowledge for investors before making financial decisions, such as investment decisions and other investment instruments, to minimise possible risks. This study is expected to be used as a source of information and learning to measure the performance of the company (issuer) and to improve the quality of the company so that it is effective and improves the welfare of the company and its customers. It is hoped that this research can be used as a source of reference and consideration as well as theories for future research.